The impact of human capital on the development of startup enterprises in Kosovo - Rexhepi, Burhan Reshat; Haziri, Artan; Kida, Nakije; Avdimetaj, Kestrim; Mustafa, Labeat; Rama, Hamëz H.; Daci, Enver (Edelweiss Applied Science and Technology, 2025)
The purpose of this study is to analyze the impact of human capital on the development and success of startup enterprises in Kosovo. In an economic context marked by structural challenges and a lack of sustainable investments, startups represent significant potential for job creation and long-term growth. However, their success is often determined by the level of human capital—a key component that includes the skills, knowledge, experience, and education of founders and employees. A quantitative methodology was employed in this study. Data were collected from 150 startup enterprises in Kosovo through structured questionnaires and analyzed using statistical methods via SPSS. The study measures the relationship between components of human capital (education, training, and experience) and performance indicators (revenue growth, number of employees, startup longevity). The findings indicate a strong positive correlation between the level of human capital and the development of startups. In particular, startups led by founders with higher education levels and prior managerial experience tend to achieve faster market expansion and operational sustainability. The theoretical implications of this research confirm the critical role of human capital in economic development models. Practically, the results offer valuable insights for policymakers and economic development institutions in designing training and education schemes tailored for entrepreneurs. The originality of this paper lies in its focus on Kosovo, a developing economy with unique cultural and institutional features. The study contributes to the existing literature by providing empirical evidence on the importance of human capital in determining startup success in a Balkan context.